Cereals and pulse-based ready-to-use therapeutic food as an alternative to the standard milk- and peanut paste–based formulation for treating severe acute malnutrition: a noninferiority, individually randomized controlled efficacy clinical trial. Issue 4 (16th March 2016) - Bahwere, Paluku; Balaluka, Bisimwa; Wells, Jonathan CK; Mbiribindi, Chobohwa N; Sadler, Kate; Akomo, Peter; Dramaix-Wilmet, Michèle; Collins, Steve
ABSTRACT: Background: The cost of current standard ready-to-use therapeutic food (RUTF) is among the major obstacles to scaling up community-based management of acute malnutrition (CMAM), an important child survival strategy. Identifying a cheaper alternative is a global public health priority. Objective: We sought to compare the efficacy of soya-maize-sorghum RUTF (SMS-RUTF) with that of standard peanut paste–based RUTF (P-RUTF). Design: We used a nonblinded, parallel-group, simple randomized controlled trial along with a day care approach that enrolled 2 groups of children aged 6–23 and 24–59 mo, respectively, with severe acute malnutrition (SAM). Results: Intention-to-treat (ITT) and per-protocol (PP) analyses showed noninferiority of SMS-RUTF compared with P-RUTF for the recovery rate [ITT: Δ = −2.0% (95% CI: −7.6%, 3.6%); PP: −1.9% (95% CI: −5.3%, 1.4%)], weight gain [Δ = −0.7 g · kg −1 · d −1 (95% CI: −1.3, 0.0 g · kg −1 · d −1 )], and length of stay [Δ = 2.0 d (95% CI: −1.7, 5.8 d)] in children ≥24 mo of age. In children ≤23 mo of age, the recovery rate of SMS-RUTF was inferior to that of P-RUTF [ITT: Δ = −20.8% (95% CI: −29.9%, −11.7%); PP: −17.2% (95% CI: −25.6%, −8.7%)]. Treatment with SMS-RUTF resulted in a greater increase in hemoglobin [0.670 g/dL (95% CI: 0.420, 0.921 g/dL); P < 0.001]. Treatment with both RUTFs resulted in the replenishment of all of the amino acids tested except for methionine. There were no differences at discharge between RUTF groups in fat mass [Δ = 0.3 kg (95% CI: −0.6, 1.6 kg); P = 0.341] or fat mass index [Δ = 0.4 kg/m 2 (95% CI: −0.3, 1.1 kg/m 2 ); P = 0.262]. By contrast, comparisons of fat-free mass indicated lower concentrations than the community controls after treatment with either of the 2 RUTFs [Δ = −1.3 kg (95% CI: −2.4, −0.1 kg) and P = 0.034 for comparison between community controls and the SMS-RUTF group; Δ = −1.8 kg (95% CI: −2.9, −0.6 kg) and P = 0.003 for comparison between community controls and the P-RUTF group]. Conclusion: SMS-RUTF can be used to treat SAM in children aged ≥24 mo to reduce the costs of CMAM programs. More research is required to optimize SMS-RUTF for younger children. This trial was registered in the Pan African Clinical Trial Registry as PACTR201303000475166.